Environmentally Friendly Reactive Washing Process: A Case Study. Issue 5 (September 2022) - Toprak-Cavdur, Tuba; Anis, Pervin; Çalışkan, Naime
Available and clean water resources in the world are decreasing day by day. Textiles is one of the industries that are consuming the highest volumes of water. For this reason, it is necessary to develop environmentally friendly textile processes within the scope of sustainability. Reactive dyeing is followed by a washing process consisting of many steps to remove unfixed/hydrolyzed dyes, which is the most preferred dyeing in the coloring of cotton products. A high amount of water is consumed in these processes. In this study, an alternative washing process was developed instead of the conventional reactive washing process. The baths, which were decided to be used according to the transmittance values of the washing baths after dyeing in light, medium, and dark shades, were used again as the first two baths of the next washings. Alternative washing did not have a negative effect on the quality parameters, namely washing and rubbing fastnesses. As a result, it was observed that the last two baths of the washing cycle could be used as the first two baths of the next washing cycle. In this case, it was predicted that approximately 40%−50% water savings could be achieved. Graphical abstract